Effect of trauma center operation on emergency care and clinical outcomes in patients with traumatic brain injury - Han Kyeol Kim; Yoon Suk Lee; Woo Jin Jung; Yong Sung Cha; Kyoung-Chul Cha; Hyun Kim; Kang Hyun Lee; Sung Oh Hwang; Oh Hyun Kim (Journal of Trauma and Injury)
Purpose Traumatic brain injury (TBI) directly affects the survival of patients and can cause long-term sequelae. The purpose of our study was to investigate whether the operation of a trauma center in a single tertiary general hospital has improved emergency care and clinical outcomes for patients with TBI. Methods The participants of this study were all TBI patients, patients with isolated TBI, and patients with TBI who underwent surgery within 24 hours, who visited our level 1 trauma center from March 1, 2012 to February 28, 2020. Patients were divided into two groups: patients who visited before and after the operation of the trauma center. A comparative analysis was conducted. Differences in detailed emergency care time, hospital stay, and clinical outcomes were investigated in this study. Results On comparing the entire TBI patient population via dividing them into the aforementioned two groups, the following results were found in the group of patients who visited the hospital after the operation of the trauma center: an increased number of patients with a good functional prognosis (P<0.001 and P=0.002, respectively), an increased number of surviving discharges (P<0.001 and P<0.001, respectively), and a reduction in overall emergency care time (P<0.05, for all item values). However, no significant differences existed in the length of intensive care unit stay, ventilator days, and total length of stay for TBI patients who visited the hospital before and after the operation of the trauma center. Conclusions The findings confirmed that overall TBI patients and patients with isolated brain injury had improved treatment results and emergency care through the operation of a trauma center in a tertiary general hospital.